(untitled) (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Vaccines require continuous monitoring to increase their compliance, quality, and safety. We conducted this study to fulfill the research gap for the adverse events following immunization (AEFIs) after COVISHIED (ChAdOx1nCoV-19) vaccination among Nepali of eastern Nepal. Method: A cross-sectional study was conducted from 25 Jan 2021 to Jul 2021 at Birat Medical College Teaching Hospital of Morang, Nepal. The data on COVISHIELD vaccine recipients at this center were analyzed for AEFI. Ethical clearance was obtained. Result: Out of 167 vaccine recipients, the mean age was 28.08±7.35 y. The AEFI occurred in 122(73.1%) and 89(72.9%) who developed symptoms on the same day of vaccination. The AEFI symptoms were less common in males (OR 0.43; CI (0.19-0.96; P 0.03). In both sexes, the AEFI symptoms were reported on the same day of vaccination than the next day but it had no significant association. Conclusion: The AEFI following COVISHIED vaccination was reported by 2/3rd recipients mostly on the same day of the vaccine and less common in males.